Far from the madding crowd - Thomas Hardy; Srinivasan, Seetha Ed (Hyderabad Orient Blackswan, 2010)
The first of Hardy's great novels, and the first to sound the tragic note for which his best fiction is remembered' Margaret DrabbleThomas Hardy's novel of swift passion and slow courtship is imbued with evocative descriptions of rural life, and with unflinching honesty about sexual relationships. Its heroine, Bathsheba Everdene, takes up her position as a farmer on a large estate, where her confident presence draws three very different suitors: the gentleman-farmer Boldwood, the soldier-seducer Sergeant Troy and the devoted shepherd Gabriel Oak. Each, in contrasting ways, unsettles her decisions and complicates her life, and when tragedy ensues, the stability of the whole community is threatened.Edited with an Introduction and notes by ROSEMARIE MORGAN with SHANNON RUSSELL
Keywords: English Fiction; English Novel